2022
DOI: 10.21608/mid.2022.129490.1264
|View full text |Cite
|
Sign up to set email alerts
|

Do CRP levels predict severity in COVID-19 hospitalized Egyptian patients?

Abstract: patients possibly acquire life-threatening complications that involve septic shock, coagulation dysfunction, and multiple organ failure [6]. According to previous several previous studies, COVID-19 progression may be aided by an abnormal immune-inflammatory response and cytokine storm [7,8].C-reactive protein (CRP) is a pentameric acute-phase reactant produced by the liver, and its level rises in response to the action of cytokines like

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
2
1
0
Order By: Relevance
“…As regard CRP level at the day of admission (CRP 1) in this research, there was high statistical significant difference between its levels (Median (IQR)) in moderate and severe group (58 (52 -89 mg/L) versus 137.5 (88 -184.5) mg/L respectively). This finding was in agreement with Moneer et al (17) who revealed that Patients showing a mean (±SD) of CRP 60.17 ±92.83 mg/L were patients regarded as moderate COVID-19 patients, while the mean (±SD) CRP level of 91.29 ±81.96 mg/L was present in severe cases with high statistical difference between them. Lentner et al (19) , found that the higher the CRP level in patients, the greater the severity of COVID-19 cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As regard CRP level at the day of admission (CRP 1) in this research, there was high statistical significant difference between its levels (Median (IQR)) in moderate and severe group (58 (52 -89 mg/L) versus 137.5 (88 -184.5) mg/L respectively). This finding was in agreement with Moneer et al (17) who revealed that Patients showing a mean (±SD) of CRP 60.17 ±92.83 mg/L were patients regarded as moderate COVID-19 patients, while the mean (±SD) CRP level of 91.29 ±81.96 mg/L was present in severe cases with high statistical difference between them. Lentner et al (19) , found that the higher the CRP level in patients, the greater the severity of COVID-19 cases.…”
Section: Discussionsupporting
confidence: 92%
“…Male patients were the majority in both studied groups. This agreed with Li and colleagues (16) and Moneer et al (17) who studied the epidemiologic data of the confirmed COVID-19 patients. Sex hormones from men and women have different effects on the immune system in the present disease.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Mayada Moneer et al . [ 8 ] concluded that serum CRP is a simple and effective laboratory marker for identifying patients at risk of developing a severe form of COVID-19. In a study by Gao Y et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wei Chen et al [7] found a direct association between the extent of severity of CT infiltration and the rising level of CRP regardless of patient age and lymphocyte count. Moreover, Mayada Moneer et al [8] concluded that serum CRP is a simple and effective laboratory marker for identifying patients at risk of developing a severe form of COVID-19. In a study by Gao Y et al [9], an average CRP level of 39.4 mg/L was detected in patients with severe COVID-19 infection, while patients with mild infection had a CRP level of 18.8 mg/L, which closely aligns with the findings of our current study.…”
Section: Discussionmentioning
confidence: 99%